Secure exchange and effectual verification of educational academic records using hyperledger fabric block chain system. (14th June 2022) - Babu, E. Suresh; Rao, M. Srinivasa; Naganjaneyulu, Satuluri; Sai, M. Srinivasa Sesha; Ganiya, Rajendra Kumar
This paper provides a solution to the educational certification issue by employing the blockchain network. The proposed permissioned blockchain network is implemented in hyperledger fabric. The proposed system provides various services to issuing institutions: verifying organisation; identification and authentication of the issuer; verify and securely share academic records to the recipients; and stores the academic records in the blockchain in a distributed manner, ensuring the privacy of stored records of the recipient. When compared to Ethereum, hyperledger fabric provides additional functionalities like efficient parallelism, concurrency, multiple transaction executions, and efficient commitments of the transaction into the ledger. The experimental analysis of the proposed system has been executed to test the performance of invoking and query transactions using Hyperledger Caliper. We analyse the throughput and transaction latency of the proposed work as well. The experimental results exhibit the proposed system achieves better transaction processing power and security compared to existing systems.